MEDICO-GENETIC DIAGNOSIS OF HEREDITARY PREDISPOSITION TO NONCARRYING OF PREGNANCY AND REPRODUCTIVE LOSSES - Rudenko, I.V.; Lihachov, V.K.; Mischenko, V.P.; Golubenko, M.Y.; Shymanska, Y.Y. (World of Medicine and Biology, 2018)
The analysis of genetic models (gene grids) of genes associated with the risk for noncarrying of pregnancy: 2 collagen (COL2A1 6846C/A), plasminogen activator inhibitor-1 (RAI-1 PLANH1), superoxide dismutase (SOD1 7958 G/A), glutathione S-transferase (GSTμ1), N-acetyltransferase 2 (NAT2) has been carried out in 327 women. Their role in reproductive losses has been shown.